Management of Trustworthy Village Owned Enterprises (BUMDES) in Improving Business and Economy through Community Empowerment of Koluwok Village, East Sumalata District, North Gorontalo Regency - Mohamad Syukur Adam; Ellys Rachman; Lisda Van Gobel (Formosa Journal of Applied Sciences, 2022)
The aim and objective of this research is to analyze the management problems of Village Owned Enterprises in Koluwoka Village, East Sumalata District, North Gorontalo Regency. The results of this study indicate that the management of Village Owned Enterprises in Koluwoka Village, East Sumalata District, North Gorontalo Regency is categorized as quite good in terms of the management process seen from the several businesses that have been carried out. However, seen from the planning aspect, the Koluwoka Village-Owned Enterprise, East Sumalata District, North Gorontalo Regency has not been optimal in its planning, coordination and supervision, even though it complies with existing provisions as stated in the Village Minister Regulation. The deficiencies in planning by the Koluwoka Village-Owned Enterprises are that there are no indicators of optimal activity plans in accordance with the main objectives of the establishment of Village-Owned Enterprises.